Pre-emergence herbicides affect seedling emergence of tropical forest tree species - de Souza, Diego Cerveira [UNESP]; Engel, Vera Lex [UNESP] (Springer Nature, 2017)
Testing techniques to reduce weed infestation is a crucial step in developing direct tree seeding systems. The use of pre-emergence herbicides may be an alternative to manual weeding techniques, but so far, information on how they affect the seeds of native tree species is scarce. We established a greenhouse experiment to evaluate the effects of four pre-emergence herbicides (atrazine, diuron, isoxaflutole and oxyfluorfen) on weed suppression and seedling emergence and early growth of seven tropical forest tree species (Annona coriacea Mart., Citharexylum myrianthum Cham., Cordia ecalyculata Vell., Peltophorum dubium (Spreng.) Taub., Psidium guajava L., Pterogyne nitens Tul. and Schinus terebinthifolia Raddi). The experimental design was a randomized complete block design with five treatments and five replicates. The treatments consisted of a single dose of each pre-emergence herbicide and a control. Throughout the 60 days after sowing we evaluated weed cover and seedling emergence and early growth of tree species. Overall, our results suggest that all tested herbicides reduced weed cover; however, they also negatively affected tree species seedling emergence. Of the four herbicides tested, atrazine and diuron showed the greatest effects on tree seedling emergence, oxyfluorfen was least aggressive towards native species and isoxaflutole was most effective in weed control. Native tree species varied in their responses to herbicides, indicating that future experiments should increase the number of species tested as well as investigate how seed traits can affect the species responses to different herbicides.
Keywords: Direct seeding; Pre-emergence herbicides; Seedling emergence; Tropical seasonal forests; Weed control